IBM TS7700 virtualization engine with R3.2 - Coyne, Larry (IBM redbooks., 2015)
This IBM® Redbooks® publication highlights IBM TS7700 Virtualization Engine Release 3.2 (IBM TS7700). IBM TS7700 is part of a family of IBM System Storage® Enterprise tape products. This book is intended for system architects who want to integrate their storage systems for smoother operation. The IBM TS7700 offers a modular, scalable, and high-performing architecture for mainframe tape virtualization for the IBM System z® environment. It integrates IBM 3592 tape cartridges, high-performance disks, and a new disk cache subsystem into a storage hierarchy. This storage hierarchy is managed by robust storage management firmware with extensive self-management capability. It includes the following advanced functions: Policy management to control physical volume pooling Cache management Redundant copies, including across a grid network Copy mode control The IBM TS7700 Virtualization Engine offers enhanced statistical reporting. It also includes a standards-based Management Interface (MI) for IBM TS7700 management. The IBM TS7700 Release 3.2 continues the next generation of IBM TS7700 Virtualization Engine servers for System z tape: IBM TS7720 features encryption-capable, high-capacity cache using 3 terabyte (TB) serial-attached Small Computer System Interface (SAS) disk drives with Redundant Array of Independent Disks (RAID) 6, providing the ability to scale to very large capacities with the highest level of data protection. IBM TS7740 features encryption-capable 600 gigabyte (GB) SAS drives with RAID 6 protection. Both models write data by policy to physical tape through attachment to high-capacity, high-performance IBM TS1140 and earlier IBM 3592 model tape drives installed in IBM TS3500 tape libraries. Physical tape support is optional on IBM TS7720. These Virtualization Engines are based on IBM POWER7® technology. They offer improved performance for most System z tape workloads compared to the first generation of IBM TS7700 Virtualization Engine servers. IBM TS7700 Virtualization Engine Release 3.2 builds on the existing capabilities of the IBM TS7700 family. It also includes the following enhancements to the IBM TS7700 family: 25 GB logical volume sizes Options for attaching back-end physical tape to IBM TS7720 systems Up to eight repository partitions in a tape-attached IBM TS7720.